The Effect Of Animated Media on Anxiety in Facing Menarche Among Students at SD Negeri 2 Ciamis - Nurjanah, Sri; Srinayanti, Yanti; Sukmawati, Ima; Lismayanti, Lilis (Asy-Syifa : Journal of Science and Technology Nursing, 2025)
Purpose: This study aims to identify the effect of animated media in reducing menarche-related anxiety among female students in grades 4, 5, and 6. Menarche, as the first experience of menstruation, often causes anxiety in young girls due to a lack of understanding and preparedness. Therefore, providing appropriate and engaging educational media is essential to help reduce anxiety levels. Methods: This study employed a pre-experimental design using a one-group pretest-posttest approach. The sample consisted of 19 female students from grades 4 to 6, selected through purposive sampling. The instrument used for data collection was an anxiety questionnaire designed to assess students’ emotional responses related to menarche. Data were analyzed using the Wilcoxon signed-rank test to determine differences in anxiety levels before and after the intervention. Results: The results showed a significant difference in the average anxiety scores between the pretest and posttest. The p-value obtained was 0.001, which is less than the significance level of 0.05, indicating that animated media had a significant effect in reducing students' anxiety about menarche. Conclusion: Animated media is effective in increasing students’ engagement and understanding of menarche, making educational messages more accessible and reducing emotional distress related to the experience